Criminological theories: introduction, evaluation, and application - Akers, Ronald L. (Oxford Univ. Press, 2009)
Introduction to criminological theory -- Deterrence and rational choice theories -- Biological theories -- Psychological theories -- Social learning theory -- Social bonding and control theories -- Labeling and reintegrative shaming theory -- Social disorganization, anomie, and strain theories -- Conflict theory -- Marxist and critical theories -- Feminist theories -- Integrating criminological theories